Hexakis [60]Fullerene Adduct‐Mediated Covalent Assembly of Ruthenium Nanoparticles and Their Catalytic Properties. Issue 54 (29th August 2017) - Leng, Faqiang; Gerber, Iann C.; Lecante, Pierre; Bentaleb, Ahmed; Muñoz, Antonio; Illescas, Beatriz M.; Martín, Nazario; Melinte, Georgian; Ersen, Ovidiu; Martinez, Hervé; Axet, M. Rosa; Serp, Philippe
Abstract: The C66 (COOH)12 hexa‐adduct has been successfully used as a building block to construct carboxylate bridged 3D networks with very homogeneous sub‐1.8 nm ruthenium nanoparticles. The obtained nanostructures are active in nitrobenzene selective hydrogenation. Abstract : Keep your distance : The synthesis of Ru nanoparticle assemblies with control of interparticle distances through covalent bonds with functional molecules is reported (see scheme). The obtained nanostructures are active in nitrobenzene selective hydrogenation.